Multivisceral resection for colon cancer with adjacent organ invasion: Whipple procedure, right hemicolectomy, and hepatic segmentectomy - Perez Carriles, Jose D.; Martinez, Marco A. G.; Rodriguez, Rosaura J. S. (International Journal of Research in Medical Sciences, 2025)
Female patient, 55 years old, with a medical history of arterial hypertension and type 2 diabetes mellitus, diagnosed with a tumor in the hepatic flexure of the colon infiltrating the duodenum, the pancreatic head, the biliary tract, and segment V of the liver. A right hemicolectomy, Whipple procedure, and hepatic segmentectomy of segment V were performed. The patient exhibited a favorable postoperative course on the first day without signs of immediate complications. This case highlights the importance of multivisceral resection in the management of advanced colon tumors with invasion into multiple organs.